Analisis Yuridis Asas Fiksi Hukum Pada Pasal 81 Undang-Undang Nomor 12 Tahun 2011 Tentang Pembentukan Peraturan Perundang-Undangan Dalam Perspektif Teori Tujuan Hukum - Jumiartis, Jumiartis; Artina, Dessy; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The existence of legal fiction actually assumes that everyone knows the law(presumtioiures de iure). However, many people really don't know about the existence of agood rule because of a lack of socialization from the government, not awareness of thepeople concerned. Van Apeldoorn introduced the principle of Legal Fiction and it has beennormalized in article 81 of Law Number 12 of 2011. In Latin there is also the adageignorantia jurist non excusat, ignorance of the law cannot be forgiven. There is also astatement with the same principle, namely the principle of ignorantia juris neminemexcusat ,that is, ignorance of the law is not a reason for forgiveness for someone. As for the sound ofArticle 81 of Law Number 12 of 2011 in terms of promulgation, it is so that everyone knowsit, and in its explanation it states that everyone is considered to know the law. The aim of thisresearch is to find out the reasons for ignorance of legal fiction by finding out what theurgency is and whether legal fiction is in accordance with legal objectives.This research method uses a type of normative legal research using qualitativeanalysis by outlining, explaining and describing the principles of legal fiction and legalobjectives. By using primary legal materials such as the 1945 Constitution, Law Number 12of 2011 concerning the Formation of Legislative Regulations replacing Law Number 10 of2004, Law Number 14 of 2008 concerning Openness of Public Information, also with aconceptual approach , and cases. Also other supporting legal materials.Fictional research results that appear to be intended more to encourage confidencethat a given legal outcome is just and appropriate are known as emotive fictions, and are anapology for the necessity in which the law finds itself in linking the actions of the parties tolegal consequences that they could not have anticipated. as apologetic fiction. However,looking at the situation in Indonesia where there are still people who do not know the law,both in terms of education, awareness of the law, knowledge and the reach of access toinformation is not optimal. So, apart from the role of the state in terms of legal education orsocialization and so on, action and understanding and improvement of the conditions asreferred to are needed.Keywords: Legal Fiction, Legislation, Legal Objectives.